Sovereign Wealth Funds and Global Economic Stability: A Strategic Approach to Asset Diversification - Pranita, Fera Lufhidarani; Aswin, Ullya Rahmi; Gustina, Leni (Journal of Economics and Management Scienties, 2025)
Sovereign Wealth Funds (SWFs) have become increasingly influential in the global financial system, serving not only as state investment vehicles but also as instruments of macroeconomic stabilization. This study explores how asset diversification strategies employed by leading SWFs—such as Norway’s GPFG, Singapore’s GIC and Temasek, the UAE’s ADIA, and Qatar’s QIA—contribute to global economic resilience. Utilizing a qualitative approach and thematic analysis, the research synthesizes insights from policy documents, academic literature, and institutional reports to assess the strategic rationale, governance structures, and risk management practices underpinning SWF operations. The findings reveal that robust asset diversification, especially when aligned with long-term mandates, transparency, and ESG integration, enhances a fund's capacity to act as a counter-cyclical buffer during economic crises. However, geopolitical influences, governance opacity, and illiquid asset exposures pose significant challenges. This study contributes to the growing discourse on sovereign investment by affirming the critical role of SWFs in promoting global economic stability, and offers policy recommendations for optimizing their structure and strategy in both developed and emerging economies.